The english language training throught songs to improve childern's learning in teluklada village: pelatihan bahasa inggris melalui lagu guna meningkatkan belajar anak di desa teluklada - Putri, Putri Malia; Idris Supriyadi; Dede Imtihanudin (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
English learning in children in the village is quite underdeveloped, as kkn students empathize so that children in the village can learn English well, making tutoring as a means is often done so that children can learn comfortably at times other than school, making singing as a learning method so that learning becomes light, the results obtained from this method are children memorizing new vocabulary, and good pronunciation.